TINJAUAN YURIDIS MASYARAKAT HUKUM ADAT DALAM HUKUM POSITIF INDONESIA - Fauzan Zakir (Ensiklopedia Sosial Review, 2022)
Definition of customary law community, a unit whose members: 1) Behave and behave as a unit towards the outside world, 2) Have a fixed and eternal structure. In the community there is no thought to dissolve the community, 3) The residents respect the life of the group as a natural thing. Customary law communities are formed naturally (natural nature), 4) Have separate property from their citizens, 5) Have authority and coercive power in the creation and development of the law (have institutions and sanctions). On May 16, 2013, the Constitutional Court issued a decision No. 35/PUU-X/2012 regarding the review of the Forestry Law. The petitioners in this case are the Alliance of Indigenous Peoples of the Archipelago (AMAN), the Indigenous Peoples of Kenegerian Kuntu, Kampar Regency, Riau Province and the Indigenous Peoples of Kasepuhan Cisitu, Lebak Regency, Banten Province. Constitutional Court Decision No. 35/PUU-IX/2012 is an important decision because it overturns the classic understanding in Indonesia about forests, forest areas and the position of customary forests. In essence, the Constitutional Court's decision concerns two constitutional issues, first regarding customary forests and secondly regarding the conditional recognition of the existence of indigenous peoples. The decision granted the request relating to customary forests, but rejected the request to abolish the conditions for recognizing the existence of indigenous peoples contained in the Forestry Law.Keywords: Customary Law Society, Positive Law, Indonesia.